Finding Our Co-: Witness Blanket as Co-curricular Making for Local Indigenous and Settler Relations (LEARNing Landscapes, 2023)
This paper reveals the journey of two settler-researcher-educators supporting learning in preparation for Carey Newman’s Witness Blanket Art Exhibit. Invited to create curriculum for students and educators of K-12 who would visit the exhibit, the authors describe co-curricular making as a living, re-generative, re-cursive experience. The learning alongside diverse perspectives of educators and community partners in circle—including Syilx Okanagan, School District, Art Gallery, Museum, and University—led to reconsidered understandings of co-curricular making. Relational commitments that invite co-curricular engagement with the Witness Blanket foreground Syilx Knowledge toward resisting colonial ways, and supporting tmixʷ, the life forces of Syilx Okanagan Territory.
Keywords: co-curricular; Indigenize; decolonize; teacher education; ethical relationality; Syilx Okanagan